Management of Malignant Solitary Fibrous Tumor of Pleura-A Diagnostic Conundrum and Literature Review - Sahni, Manish; Katiyar, Dinesh Chandra; Karande, Snehal Kailas; Chakraverty, Jyoti (Asian Pacific Journal of Cancer Care, 2025)
Introduction and Importance-Solitary fibrous tumors are rare neoplasms originating from CD34+ dendritic stromal cells with pleural cavity as the the most common site. Majority of them are benign and 10%−20% cases are malignant. This case report contributes to the sparse literature by detailing diagnostic and therapeutic approaches, emphasizing the role of surgical resection and adjuvant therapies. Case presentation-69-year-old gentleman presented right sided chest heaviness for last 3 months. Investigations-CT scan chest revealed 13.6×13.0 x15.0cm right sided pleural based mass. Interventions and Outcome-CT guided biopsy of pleural based mass revealed solitary fibrous tumor with IHC marker positive for STAT6 and CD34. He underwent en bloc excision of mass with right upper and middle lobectomy via posterolateral thoracotomy. Patient had air leak on postoperative day 5 which was managed successfully by bronchoscopic guided glue instillation over apical lobe bronchus stump. Final histopathology showed solitary fibrous tumor with high risk of metastasis based on nuclear atypia, tumor necrosis, mitosis. Patient received adjuvant radiotherapy with the total dose of 50 Gy in 25 fractions. He is now on regular follow up every 6 monthly and is now disease from last 1 year. Relevance and Impact-Malignant solitary fibrous tumor of the pleura is a rare mesenchymal neoplasm with diagnosis primarily based on immunohistochemical study. Complete surgical resection remained the first-line treatment of MSFTP with radiotherapy reserved for patients with positive resection margin and malignant solitary fibrous tumor. Future randomized control trials are required to better understand the therapeutic approaches of this entity. This case report also highlights the successful role of bronchoscopic instillation of glue over air leak site.